Sociodemographic and Health Profile of the Elderly in the city of João Pessoa - PB - Laryssa Dantas Dias; Geraldo Eduardo Guedes de Brito; Franklin Delano Soares Forte; Kalina Menezes Brindeiro de Araújo; Eleazar Marinho de Freitas Lucena (Universidade de Fortaleza, 2012)
Objective: To explore the sociodemographic profile and physical health of elderly enrolled in Family Health Units (USF) in the city of João Pessoa - PB, Brazil, and the factors associated with self-reported diagnoses in this population. Methods: The sample consisted of 401 elderly aged 60 years or more enrolled in USF, selected through a random drawing of families' medical charts. A semi-structured questionnaire was applied to collect data.Prevalence rates and their related IC 95% were calculated for sample characterization and chi-square test was used to verify heterogeneity among the proportions. Results: In the assessed population, 67.6% (n=271) were female, 53.6% (n=215) were aged 60-69 and 54.9% (n=220) were married. Regarding health conditions, 50.4% (n=202) self-perceived their health as fine and 52.1% (n=209) displayed some degree of dependence to perform instrumental activities of daily living (IADL). Significant association was found (p>0.005)between the number of self-reported diagnoses and gender, self-rated health, amount of medicine ingestion per day and instrumental activities of daily living. Conclusions: The profile of population reveals predominance of women, aged 60-69 years, married, livingwith a maximum of five people, the children being the ones with the strongest linkage to the elderly, with just over half of the sample not knowing how to read and write, and total household income in the interval of two and three minimum wages. The elderly also showedindependence to perform activities of daily living and light or moderate degree of dependence to perform at least one of the instrumental activities of daily living.